Stimulating University Student Entrepreneurship: Evidence from an African Developing Country - Ayiku, Andrews; Grant, E. Stephen; Mensah, Prince Kofi (Journal of Comparative International Management)

(untitled) (Management Futures, 2022)
Entrepreneurship education at the tertiary level is gaining ground within developing economies like Ghana. But empirical studies that assess the role of universities in stimulating and consolidating entrepreneurship traits are limited in emerging economies. This study is a quantitative study that adopts the structural equation model approach to examine the effect of four constructs (Attitude, Subjective Norm, Perceived Behavioral Control, and the Role of University) on the Entrepreneurship Intention of university students in Ghana. Results indicate a significant positive relationship between university entrepreneurial role and student entrepreneurial intention. Also, both attitude and subjective norm had a significant positive association with student entrepreneurial intention. The relationship between perceived behavioral control and student entrepreneurial intention was a significant negative relationship. These results provide an empirical basis for leveraging universities to stimulate students’ entrepreneurial intention within developing economies such as Ghana.